Information Flow and Pricing Errors: A Unified Approach to Estimation and Testing - George, Thomas J.; Hwang, Chuan-Yang (Review of Financial Studies, 2001)
This study examines whether rates of information flow differ between trading and nontrading periods, and whether the variances of pricing errors differ at the open and close of trading. The approach improves on existing methods by allowing for correlation between pricing errors and information flow, and by conducting inferences at the individual security level. The daytime rate of information flow is about seven times the overnight rate, and the variances of pricing errors at the open are not different from those at the close of trading. This evidence differs from existing results based on return variance ratios. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.